Incorporating the participatory process in the design of geospatial support tools: Lessons learned from SeaSketch. (May 2020) - Burnett, Charla M.
Abstract: Since launching five years ago, SeaSketch has been used in approximately 30 large-scale projects and over 200 educational programs and research-based initiatives distributed over 40 countries. The study presented in this article engages SeaSketch developers, project administrators, and users through semi-structured interviews and surveys meant to inform designers on how to better incorporate the participatory process within geodesign applications. The results of this study suggest five ways in which designers can help increase public participation including: (1) determining the eligibility of a project by mapping stakeholder engagement, (2) monitoring perceptions of fairness, (3) visualizing data for non-technical experts, (4) alternatives to usability models with chauffeurs, and (5) project management features within geodesign. Each one of these suggestions provides ample avenues of inquiry and can help practitioners and researchers conduct longitudinal studies across projects and/or applications. Highlights: The results of this study suggest five ways in which designers can help to increase public participation. This study uses in-person interviews and survey methods to gather the experiences and perceptions of geodesign developers, project administrators, and users. Monitoring perceptions of fairness continues to be a crucial element of public participatory geographic information systems. Alternative usability models need to be created for users that are guided by representatives, known as 'chauffeurs.'